Fabrication of polymeric optical waveguides by B-Staged Bisbenzocyclobutene(BCB) - Shee, Yu Gang; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Ibrahim, Mohd. Haniff (IEEE, 2004)
This paper reports the fabrication of polymeric optical waveguides. Single mode planar slab waveguides and straight waveguides had been fabricated from the organic polymer B-staged bisbenzoeyclobutene (BCB) from DOWO Chemical. A low cost fabrication method, chemical etching is used to form the waveguides on BK7 glass substrates. The processing conditions required for the fabrication of single mode optical waveguides are presented.